Dividends, ownership structure and board governance on firm value: empirical evidence from Malaysian listed firms / Zunaidah Sulong, Fauzias Mat Nor - Sulong, Zunaidah (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
This paper aims to examine the effects of dividends, types of ownership structure and board governance on Malaysian firm's value using sample of 406 listed firms on the Main Board of Bursa Malaysia. A cross-sectional analysis for the years 2002 and 2005 was utilised. Both direct effects as well as the moderating effects of board governance with dividends and types of ownership structure are examined. The moderating relationship is considered in order to investigate the board governance role after the implementation of the Malaysian Code of Corporate Governance through the amendments of Bursa Malaysia Listing Requirements in 2001. Result from the direct effect reveals that dividend has a significant positive effect to firm value in both years, thus supporting the expected hypothesis. This finding is consistent with the view that dividends mitigate agency costs of free cash flow problem, therefore, increase firm value. The finding also suggests that dividends among Malaysian listed firms can play its important monitoring role in reducing agency costs. However, contrary to expectation, government ownership indicates significantly positive relationship. Correspondingly, the result implies that investors in the Malaysian market do value the higher standards of corporate governance reform found in the government-controlled firms. In addition, foreign ownership has a negative significant relationship to firm value which is also contrary to what is expected. Surprisingly, results on ownership concentration and managerial ownership provide insignificant effect to firm value for both years. Of particular interests are the results of moderating effects, the result reveals that board duality has significantly moderated the relationship between dividends and firm value with a lower coefficient positive effect as expected. Thus, support the expected hypothesis. As expected, the result from the moderating effect of board duality with government ownership in year 2002 provided negatively significant result. However, both results of board duality with dividends and government ownership provide insignificant effect for the year 2005. Further, the interaction term between dividends with board independence was positively significant for the year 2005. Whereas, the interaction term between dividends and board size showed significantly lower coefficient positive moderating effect for both years. Finally, the inclusion of board size interaction term to foreign ownership provided significantly negative moderating effect in year 2002. Overall, findings from this paper reveal that good board governance; particularly board independence and board size can enhance the monitoring role of dividends, government, and foreign ownership in reducing agency costs, thus increasing firm value.